Dental amalgam associated with SAPHO syndrome and IgA nephropathy: a case report and literature review - Yan Cai; Qingqing You; Weina Jiang; Xuyan Liu; Leping Shao (BMC Nephrology)
Abstract Background Exposure to metals is associated with adverse health effects, including multiorgan damage and dysregulation of systemic immune responses. The increasing use of metallic implants in humans, such as dental materials and orthopedic devices, has resulted in chronic endogenous exposure to metal ions. The pathophysiological mechanisms underlying implant-related complications and their clinical implications have not been fully elucidated. Case presentation We present a case of synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome coexisting with IgA nephropathy (IgAN) in the context of dental amalgam exposure. Following amalgam placement, the patient developed palmoplantar pustulosis (PPP) and sternoclavicular arthritis, with a subsequent diagnosis of IgAN. Notably, all the clinical manifestations were markedly resolved after amalgam removal. Conclusion This case suggests a potential link between SAPHO syndrome, IgAN, and dental amalgam exposure. To our knowledge, this is the first reported case linking these conditions. Further studies are needed to elucidate the mechanisms and clinical implications of metal-induced autoimmune or inflammatory responses. Clinical trial number Not applicable.